Magnitude and relevance of change in health-related quality of life in patients with vascular malformations treated with sirolimus - Harbers, Veroniek E. M.; Bouwman, Frédérique C. M.; van Rijnsoever, Ingrid M. P.; Verhoeven, Bas H.; van der Vleuten, Carine J. M.; Schultze Kool, Leo J.; de Laat, Peter C. J.; van der Horst, Chantal M. A. M.; Kievit, Wietske; te Loo, D. Maroeska W. M. (Frontiers in Medicine, 2023)
Introduction Vascular malformations are rare congenital anomalies of the vascular system, which can involve the capillaries, veins, arteries, lymphatics, or a combination of vessel types. Patients with vascular malformations experience an impaired health-related quality of life (HRQoL) because of their symptoms (e.g., pain, swelling, and bleeding) and psychosocial distress. Sirolimus is an effective drug used in the medical treatment of these patients; however, relatively little is known about the effect of sirolimus on specific changes in the HRQoL domains and its magnitude. Methods The magnitude of change (effect size) following intervention is more informative to clinical practitioners than statistically significant but clinically unimportant changes; therefore, this study aimed to examine the magnitude and meaningfulness of change in the HRQoL of children and adults with vascular malformations following sirolimus treatment using low target levels. Results In total, 50 patients with vascular malformations (19 children, 31 adults) were included in this study. These patients experienced a lower HRQoL than the general population, with the adults reporting a significantly lower score in almost all domains. A 6-month sirolimus treatment improved the HRQoL in 29 patients, including 77.8% of the children (Pediatric Quality of Life Inventory score [PedsQL]) and 57.7% of the adults (Short Form 36 [SF-36]). The effect sizes of sirolimus for each SF-36/PedsQL domain ranged from 0.19 to 1.02. The clinically relevant moderate magnitude of changes was seen in the domains of the children's reports: “Physical functioning” and “Social functioning” and in the domains of the parent reports: “Social functioning,” “School functioning,” and “Psychosocial.” A high-magnitude change was seen in the domains “Emotional functioning” and “Psychosocial” in the children's reports and “Physical functioning” in the parent reports. In addition, the moderate magnitude of changes was also seen in the adults SF-36: in all domains except for “Role limitations—physical problems,” “Role limitations—emotional problems,” and “General health perception.” Conclusion We believe this is the first study showing the magnitude of change in HRQoL after sirolimus treatment in patients with vascular malformations. Before treatment, these patients experienced an impaired HRQoL compared with the general Dutch population. A 6-month sirolimus treatment with low target levels led to moderate-to-high clinically relevant changes in multiple domains, which significantly improved the HRQoL. Clinical trial registration https://clinicaltrials.gov/ct2/show/NCT03987152?cond=Vascular+Malformations&cntry=NL&city=Nijmegen&draw=2&rank=1, identifier: NCT03987152.